An investigation of the endocrine disrupting potential of enniatin B using in vitro bioassays. Issue 2 (4th March 2015) - Kalayou, Shewit; Ndossi, Doreen; Frizzell, Caroline; Groseth, Per Kristian; Connolly, Lisa; Sørlie, Morten; Verhaegen, Steven; Ropstad, Erik
Highlights: Endocrine disruption potential of ENN B was investigated using primary and cell lines. ENN B modulates cell viability and cell cycle distribution. Effect on steroid production in Leydig cells was observed only at higher concentrations used. ENN B reduced hormone production and modulated steroidogenic genes in adrenal H295R cells. No specific (ant) agonistic responses observed at the receptor level. Abstract: Evidence that some of the fungal metabolites present in food and feed may act as potential endocrine disruptors is increasing. Enniatin B (ENN B) is among the emerging Fusarium mycotoxins known to contaminate cereals. In this study, the H295R and neonatal porcine Leydig cell (LC) models, and reporter gene assays (RGAs) have been used to investigate the endocrine disrupting activity of ENN B. Aspects of cell viability, cell cycle distribution, hormone production as well as the expression of key steroidogenic genes were assessed using the H295R cell model. Cell viability and hormone production levels were determined in the LC model, while cell viability and steroid hormone nuclear receptor transcriptional activity were measured using the RGAs. ENN B (0.01–100 μM) was cytotoxic in the H295R and LC models used; following 48 h incubation with 100 μM. Flow cytometry analysis showed that ENN B exposure (0.1–25 μM) led to an increased proportion of cells in the S phase at higher ENN B doses (>10 μM) while cells at G0 /G1 phase were reduced. At the receptor level, ENN B (0.00156–15.6 μM) did not appear to induce any specific (ant) agonistic responses in reporter gene assays (RGAs), however cell viability was affected at 15.6 μM. Measurement of hormone levels in H295R cells revealed that the production of progesterone, testosterone and cortisol in exposed cells were reduced, but the level of estradiol was not significantly affected. There was a general reduction of estradiol and testosterone levels in exposed LC. Only the highest dose (100 μM) used had a significant effect, suggesting the observed inhibitory effect is more likely associated with the cytotoxic effect observed at this dose. Gene transcription analysis in H295R cells showed that twelve of the sixteen genes were significantly modulated ( p < 0.05) by ENN B (10 μM) compared to the control. Genes HMGR, StAR, CYP11A, 3βHSD2 and CYP17 were downregulated, whereas the expression of CYP1A1, NR0B1, MC2R, CYP21, CYP11B1, CYP11B2 and CYP19 were upregulated. The reduction of hormones and modulation of genes at the lower dose (10 μM) in the H295R cells suggests that adrenal endocrine toxicity is an important potential hazard.